Framework for the Business Transformation Towards the Circular Economy: A Systematic Literature Review - Rasor, Anja; Petzke, Lisa Irene; Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman (Springer Proceedings in Business and Economics)
In the face of climate change and growing sustainability awareness, industrial companies are at a pivotal point in transforming from a linear to a circular economy (CE) model. Yet, aligning their business with the principles of the CE is a challenging task. Utilizing a systematic literature review (SLR) and thematic analysis a framework for the business transformation towards the CE has been developed. It considers the dimensions product, business strategy, corporate management, and value chain. The circular business transformation (CBT) framework includes incentives for entering the CE, fields of action, design options, and associated challenges. For researchers, it provides a comprehensive overview and serves as a basis for in-depth studies of each dimension of CBT. Furthermore, it acts as a practical guide that enables industrial companies to strategically navigate through the complexity of the CBT and to effectively design it.
Keywords: Circular Economy; Circularity; Holistic View; Circular Transformation; Circular Management

Essen in der Vielfalt – Esskultur und Nahrungszubereitung - Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Die Nahrungszubereitung als zentraler Bestandteil eines haushaltsbezogenen Unterrichts dient der Anbahnung von Kompetenzen für die Zubereitung von Speisen und die Gestaltung von Mahlzeiten unter Berücksichtigung von Gesundheit und Nachhaltigkeit. Ebenso bedeutsam, jedoch häufig vernachlässigt, ist die Berücksichtigung unterschiedlicher Esskulturen, lebensweltlicher Erfahrungen und sozioökonomischer Hintergründe der Lernenden.

ReconOS64 - Hardware-Software Multithreading for Heterogeneous Platform FPGAs - Clausing, Lennart
Heterogeneous computing devices comprising multiple processing systems combined with a programmable logic like an FPGA have become increasingly popular. Developing and runtime managing these heterogeneous platform devices, however, still poses multiple challenges. The programming paradigms for hardware and software applications fundamentally differ, while the runtime management requires additional attention. The first steps towards unifying design flows have been taken by creating high-level synthesis tools. However, these toolsfocus on the design process and lack runtime management features. FPGA operating systems aim to close this gap by providing runtime management features and build tools. ReconOS, as an example of an FPGA operating system, allows bridging the hardware-software gap by integrating hardware-located computation units as threads into a host operating system, allowing for familiar inter-thread programming paradigms to be extended to FPGAs. This thesis presents ReconOS64, a successor and fork of ReconOS, aiming at modern 64-bit platform systems-on-chip. Besides establishing support for this platform and incorporating new system generation processes, ReconOS64 provides additional features for both development and runtime management. By providing a flexible grouping mechanism for hardware-located threads, partial reconfiguration for exchanging individual threads at runtime is simplified. Further runtime flexibility was achieved by implementing a multi-clock architecture, allowing individual groups of threads to be executed at different frequencies, which can be adapted during runtime with a low reconfiguration overhead. In addition, this thesis provides an overview of further development approaches on various systems based on ReconOS64 and ReconOS.

Modeling and optimization of energy system components equipped with phase change materials - Grabo, Matti
Diese Arbeit behandelt die Modellierung und Optimierung von mit Phasenwechselmaterialien (PCM) ausgestatteten, energietechnischen Komponenten anhand zweier Fallstudien. PCM sind Materialien, deren Phasenwechseleigenschaften während des Schmelzens und Erstarrens für Heiz- und Kühlzwecke genutzt werden. Zunächst werden die theoretischen Grundlagen zu Wärmeübertragungsproblemen mit Phasenwechsel erörtert und entsprechende numerische Lösungsmethoden diskutiert. Ein Modell für Phasenwechselvorgänge wird vorgestellt, welches anhand analytischer Lösungen validiert wurde und in den Fallstudien zum Einsatz kam. Für beide Fallstudien wird der Stand der Technik erörtert und die entsprechenden Forschungsfragen werden formuliert. Die erste Fallstudie behandelt PCM-integrierte Photovoltaikmodule und die zweite Festbett-Latentwärmespeicher, welche nicht-kugelförmiger PCM-Kapseln verwenden. Für beide Systeme wurden thermische Model-le entwickelt und anhand experimenteller Daten mit guter Genauigkeit validiert. Diese Modelle wurden in Parameterstudien eingesetzt, um optimierte Systemkonfigurationen zu identifizieren. Die vorgestellten Ergebnisse zeigen, dass ein PCM-Kühlkörper mit ausreichender Dicke und Wärmeleitfähigkeit den Wirkungsgrad und die Lebensdauer von Photovoltaikmodulen erheblich erhöht. Darüber hinaus verbessern PCM-Kapseln mit hoher Packungs-dichte und Oberfläche sowohl die volumenspezifische Speicherkapazität als auch die thermische Leistung von Festbett-Latentwärmespeichern.
Keywords: Heat transfer; PCM; numerical simulation; renewable energy; heat storage

Distributed Algorithms for Modern Communication Networks - Götte, Thorsten
In dieser Arbeit betrachten wir algorithmische Lösungen für fundamentale Probleme in modernen Kommunikationsnetzen. Im ersten Teil dieser Arbeit zeigen wir, wie man ein Overlay-Netzwerk mit Grades und Durchmesser O(log n) in O(log n) Runden ausgehend von einem beliebigen, schwach verbundenen Graphen konstruiert. Wir gehen von einem synchronen Kommunikationsnetz aus, in dem Knoten Nachrichten an alle Knoten senden können, deren Adresse sie kennen, und neue Verbindungen durch das Versenden dieser Adressen hergestellt werden können. Wenn der Ausgangsgraph des Netzwerks schwach zusammenhängend ist und einen konstanten Grad hat, dann konstruiert unser Algorithmus die gewünschte Topologie mit hoher Wahrscheinlichkeit in O(log n) Runden, wobei in jeder Runde nur O(log n) Nachrichten sendet und empfängt. Da das Problem nicht schneller gelöst werden kann als durch sogenanntes Pointer Doubling für O(log n) Runden (was sogar erfordern würde, dass jeder Knoten Ω(n) Bits kommuniziert), ist unser Algorithmus asymptotisch optimal. Außerdem zeigen wir, wie unser Algorithmus zur effizienten Lösung von Graphenproblemen im HYBRID modelverwendet werden kann. Motiviert durch die Idee, dass Knoten zwei verschiedene Arten der Kommunikation besitzen, nehmen wir an, dass die Kommunikation der Kanten unbeschränkt ist, während nur polylogarithmisch viele Nachrichten über Kanten gesendet werden können, die während der Ausführung eines Algorithmus etabliert wurden. Für einen (ungerichteten) Graphen G mit beliebigem Grad zeigen wir, wie man zusammenhängende Komponenten und einen Spannwald mit hoher Wahrscheinlichkeit in O(log n) Zeitberechnen kann. Außerdem zeigen wir, wie man ein MIS mit hoher Wahrscheinlichkeit in O(log ∆ + log log n), berechnet, wobei ∆ der Grad von G ist. Im zweiten Teil der Arbeit betrachten wir das Problem der Berechnung von kompakten Routing-Tabellen und Dekompositionen mit geringem Durchmesser für einen (gewichteten) Graphen G := (V, E, ℓ), der durch k kürzeste Wege separiert werden kann. Zu dieser Klasse von Graphen gehören planare Graphen, Graphen mit beschränkter Treewidth und Graphen, die einen festen Minor Kr ausschließen. Wir präsentieren Algorithmen im CONGEST- und im neuartigen HYBRID-Kommunikationsmodell, die in allen relevanten Parametern konkurrenzfähig sind:• Für einen gegebenen Parameter ϵ > 0 berechnen wir ein Routing-Schema mit Stretch 1 + ϵ. Unser Schema berechnet Label der Größe Oe(kϵ−2) und wird in Oe(kϵ−3) Zeit im HYBRID-Modell, und Oe(kϵ−3· HD) Zeit in CONGEST. Dabei bezeichnet HD den Hopdurchmesser des Graphen.• Für einem Parameter D > 0 unterteilt unser Algorithmus zur Dekomposition den Graphen in zusammenhängende Subgraphen mit starkem Durchmesser D. Eine Kante e ∈ E der Länge ℓe hat ihre Endpunkte in zwei verschieden Subgraphen mit der Wahrscheinlichkeit O(ℓe·log(k log n)/D). Die Dekomposition kann in Oe(k) Zeit im HYBRID-Modell und O˜(kHD) Zeit in CONGEST berechnet werden. Wir stellen verteilte und parallele Implementierungen von sequenziellen Divide-and-Conquer-Algorithmen vor, bei denen wir exakte kürzeste Pfade durch approximative kürzeste Pfade ersetzen. Im Gegensatz zu exakten Pfaden können diese in der verteilten und parallelen Umgebung effizient berechnet werden. Außerdem, zeigen wir, dass es ausreicht, anstelle der expliziten Berechnung von Vertex-Separatoren, einige zufällige Pfade begrenzter Länge zu wählen und die Separatoren um diese herum zu konstruieren. Schließlich stellen wir einen SetCover-Algorithmus für das Beeping-Modell vor. Unser Algorithmus läuft in O(k3) Zeit und hat eine erwartete Approximationsgüte von O(∆3/k log2 ∆). Der Wert k ∈ [3, log ∆] ist ein Parameter, mit dem wir Laufzeit gegen Approximationsgüte eintauschen können, ähnlich wie bei dem Algorithmus von Kuhn und Wattenhofer [PODC ’03]. Dieser Algorithmus kann erweitert werden, um das DominatingSet-Problem in der D-Nachbarschaft eines Graphen mittles eines verteiltes Algorithmus effizient zu lösen.

Second-order nonlinear piezo-optic properties of single crystal lithium niobate thin films - Pionteck, Mike N.; Roeper, Matthias; Koppitz, Boris; Seddon, Samuel D.; Rüsing, Michael; Padberg, Laura; Eigner, Christof; Silberhorn, Christine; Sanna, Simone; Eng, Lukas M. (Physical Review B)
Stress plays a crucial role in thin films and layered systems, and thus significantly influences the material's electrical, mechanical and (nonlinear) optical responses. Despite lithium niobate's wide applicability as a nonlinear optical material, the impact of mechanical stress on its nonlinear optical properties is not well characterized. In this work, we systematically study both experimentally and theoretically, the nonlinear optical responses of thin film lithium niobate (TFLN) single crystals. Compressive and tensile stress is applied in our experiment using a piezodriven strain cell. We then record the second-harmonic-generated (SHG) response in back-reflection geometry, and compare these results to theoretical modeling using density functional theory (DFT). Both methods consistently reveal that uniaxial stress induces changes of the nonlinear optical susceptibility of certain tensor elements on the order of up to 1 pm/(V GPa). The exact value depends on the tensor element that is addressed in our SHG analysis, on the crystal orientation, and also whether using compressive or tensile stresses. Furthermore, a lowering of the crystal symmetry when applying stress along the <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"><a:mi>x</a:mi></a:math> or <b:math xmlns:b="http://www.w3.org/1998/Math/MathML"><b:mi>y</b:mi></b:math> crystallographic axes is observed by the appearance of new nonlinear optical tensor elements within the strained crystals.

Solutions and Technologies for Responsible Digitalization

Cross-sectional association between the isocaloric replacement of carbohydrates with protein and fat in relation to fat compartments distribution and hepatic lipid content in recent-onset type 1 and type 2 diabetes. - Lang, A; Schaefer, E; Kupriyanova, Y; Goletzke, J; Weber, KS; Buyken, Anette; Kahl, S; Zaharia, OP; Herder, C; Schrauwen-Hinderling, VB; Kuss, O; Wagner, R; et al. (Nutr J)

Circadian eating patterns track from infancy to pre- and primary school-age, but are not prospectively associated with body composition in childhood - Results of the DONALD cohort study. - Perrar, I; Hohoff, E; Lesani, A; Schmitting, S; Libuda, Lars; Krüger, Bettina; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Alexy, U; Jankovic, N (Eur J Nutr)

Dietary Sugar Intake and Incident Type 2 Diabetes Risk: A Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies. - Della Corte, KA; Bosler, T; McClure, C; Buyken, Anette; LeCheminant, JD; Schwingshackl, L; Della Corte, D (Adv Nutr)

Bread, wholegrain consumption and weight change from middle to late adulthood: a prospective cohort study. - Revheim, I; Sabir, Z; Dierkes, J; Buyken, Anette; Landberg, R; Alten, I; Spielau, U; Rosendahl-Riise, H (Eur J Nutr)

Effectiveness of leader-targeted stress management interventions: A systematic review and meta-analysis. - Dannheim, I; Ludwig-Walz, H; Kirsch, H; Bujard, M; Buyken, Anette; Richardson, KM; Kroke, A (Scand J Work Environ Health)

Blogpost: "Berlin als Jewish Space? Perspektiven der jüdischen Gegenwartsliteratur" - Spener, Anna Maria

Cryogenic feedforward of a photonic quantum state - Thiele, Frederik; Lamberty, Niklas; Hummel, Thomas; Lange, Nina Amelie; Procopio Peña, Lorenzo Manuel; Barua, Aishi; Lengeling, Sebastian; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Modulation conditioned on measurements on entangled photonic quantum states is a cornerstone technology of optical quantum information processing. Performing this task with low latency requires combining single-photon-level detectors with both electronic logic processing and optical modulation in close proximity. Here, we demonstrate low-latency feedforward using a quasi-photon-number-resolved measurement on a quantum light source. Specifically, we use a multipixel superconducting nanowire single-photon detector, amplifier, logic, and an integrated electro-optic modulator in situ below 4 K. We modulate the signal mode of a spontaneous parametric down-conversion source, conditional on a photon-number measurement of the idler mode, with a total latency of (23±3)ns. Furthermore, we investigate the resulting change in the photon statistics. This represents an important benchmark for the fastest quantum photonic feedforward experiments comprising measurement, amplification, logic, and modulation. This has direct applications in quantum computing, communication, and simulation protocols.

Muhammad as a Prophet of Late Antiquity: The Anti-Apocalyptic Nature of Muhammad’s Prophetic Wisdom - Ghaffar, Zishan (Theology of Prophecy in Dialogue: A Jewish-Christian-Muslim Encounter)

Impact of the parameter distribution on the predictive quality of metamodels for clinch joint properties - Einwag, Jonathan-Markus; Mayer, Yannik; Goetz, Stefan; Wartzack, Sandro (Materials Research Proceedings)
Abstract. The growing significance of lightweight design, reveals drawbacks of conventional joining processes such as welding, which are known to consume a considerable amount of energy. This fosters the use of mechanical joining processes including clinching. However, the lack of universally applicable design methods results in a cost- and time-intensive design process. The utilization of machine learning methods can overcome these drawbacks. To ensure a reliable clinch joint design, inherent uncertainties of the design parameter such as tool deviations need to be considered in the design process. Varying distributions of design parameters, due to changes in the manufacturing process, can lead to high-computational effort in recalculating the resulting clinch joint properties with numerical simulations. Current metamodel-based methods for consideration of inherent uncertainties within the design parameters do not investigate the transferability of metamodels to different distributions of design parameters, which can lead to incorrect predictions. Therefore, this contribution investigates the performance of several metamodels on differently distributed design parameters. The obtained results indicate that metamodels demonstrate the best performance when training and evaluation distributions are identical and that polynomial regression models perform best on disparate distributions, when trained on uniform distributions.

Theology of Prophecy in Dialogue: A Jewish-Christian-Muslim Encounter
This volume examines the Rabbinic, Qur’anic and Christian understandings of prophecy from a historical and comparative theological perspective. The Rabbinic perspectives on the phenomenon of prophecy are analyzed in their historical continuity and engagement with the theological traditions of Islam and Christianity. The examination of female prophecy also occupies a central place here. Similarly, several contributors describe the deep roots of Qur’anic prophetology in the Christian and Jewish traditions of Late Antiquity and the Arabic context. Finally, the anthology attempts to reflect on these different theological traditions of prophecy in the Christian, Jewish, and Qur’anic traditions from a comparative theological perspective and to discuss the possible theological significance of this phenomenon in the modern age.

Very mild diffusion enhancement and singular sensitivity: Existence of bounded weak solutions in a two-dimensional chemotaxis-Navier–Stokes system - Black, Tobias (Journal of Differential Equations)

Emotionsreflexion als Element universitären Lehrens und Lernens Emotional reflection as an element of university teaching and learning - Lehberger, Regine (Zeitschrift für Hochschulentwicklung)
Fähigkeiten zur Wahrnehmung und Regulation von Emotionen sind von besonderer Relevanz für Studierende, da Fördermaßnahmen im Bereich der Emotionsregulation auch positive Effekte auf die Studienqualität, den Studienerfolg und die allgemeine Persönlichkeitsentwicklung haben können. Jedoch wird diesem Thema wenig Aufmerksamkeit geschenkt und hochschuldidaktisch steht die Gestaltung von kognitiven und inhaltsbezogenen Lernarrangements im Zentrum. Die Einbindung von Gelegenheiten zur Emotionsreflexion in die Lehre bietet eine niederschwellige Maßnahme zur Förderung emotionaler Kompetenzen, weshalb im vorliegenden Beitrag ein Instrument zur Umsetzung dieser Aufgabe vorgeschlagen wird.
Keywords: Emotionsreflexion; Studierende; Hochschullehre; Reflexion

MO-IOHinspector: Anytime Benchmarking of Multi-objective Algorithms Using IOHprofiler - Vermetten, Diederick; Rook, Jeroen; Preuß, Oliver Ludger; de Nobel, Jacob; Doerr, Carola; López-Ibáñez, Manuel; Trautmann, Heike; Bäck, Thomas (Evolutionary Multi-Criterion Optimization - 13th International Conference, EMO 2025, Canberra, ACT, Australia, March 4-7, 2025, Proceedings, Part I)